Measuring self-rated social health of Iranians: a population based survey in three cities - Kambiz Abachizadeh; Soheila Omidnia; Ahmad Hajebi; Ali Asadi; Maryam Rassouli; Bagherzadeh Leila (Novelty in Biomedicine, 2014)
Abstract: Background and objectives: Social health as third dimension of health, along with physical and mental health, has drawn more attention in recent years among policy makers and health system managers. No other study, to our knowledge, has documented measuring individual-level social health in Iran. In response to this need, our study tends to assess Iranians self-rated social health through conducting a survey in 3 cities of Iran.   Methods: We conducted a survey using cross sectional method in three cities of Iran included people more than 18 years old. We use a random sample size of 800 people. The scale provides a total score of social health and three sub-scores. Total score was calculated by summing all 33 items, so the range was between 33 to 165, considering that higher score indicating better social health. Psychometric parameters of scale were acceptable. To interpret scores, respondents were categorized into five ordered groups as quintiles for amount of social health. To compare social health scores in different demographic groups multiple linear regression was employed to interpret association between demographic variables and social health score.   Results: From a pool of 800 persons, 794 (99%) agreed to participate and filled out the questionnaire completely.  The mean of self-rated social health score was 105.0 (95% confidence interval, 103.8 to 106.2). 50% of participants had medium level of social health. social health score was higher for those who live in Urmia as a small city in comparison with big cities- Tehran and Isfahan (P V< 0.001) and was lower for unemployed people (PV= 0.029). There was no association between social health score and other factors such as sex, age and educational level (PV>0.05)   Conclusion: This study may be considered as the first step in evidence-based policy-making in the field of social health in Iran. Certainly, it is necessary to conduct more studies to measure social health and its determinants in a nation-wide approach.